RF7 Prevalence of chronic obstructive pulmonary disease (COPD) in greater glasgow and clyde: an ecological study by age, sex, socioeconomic and smoking status. (September 2018) - Levin, KA; Milligan, M; Anderson, D
Abstract : Background: Previously it was estimated that Greater Glasgow and Clyde (GGC) had a COPD prevalence of 2.4%. COPD has traditionally been associated with males and those from deprived areas. Socioeconomic inequalities in COPD have been largely linked to socioeconomic inequalities in smoking, the most important risk factor for COPD in high income countries. This study aims to calculate the prevalence of COPD in GGC by age, sex, and SES adjusting for smoking status. Methods: Quality and Outcomes Framework (QOF) electronic records until May 2016 were linked to mortality data. COPD Prevalence was calculated by sex, age group (10-year age bands), and SES using SIMD quintiles. Smoking status (ever smoked and current smoker) was also collected by the QOF. Population estimates for smoking status by age sex and SIMD for GGC were calculated using three Scottish Household Survey rounds, 2013, 2014 and 2015. COPD prevalence rates by SIMD quintile were calculated, adjusting for age, sex, and smoking status. Results: Crude prevalence of COPD among all ages in GGC is 2.74% and among those aged 40 years+ in GGC was 5.67%, higher in females 5.95% than males, 5.36%. Comparing prevalence of COPD between males and females, rates were higher for males until age 39 and equivalent for ages 40–49 years. However, for 50–59 year olds prevalence among females was 3.84 compared with 3.15 among males, and for 60–69 year olds, prevalence was 8.15% for females compared with 7.26% for males. Thereafter prevalence was greater among males; for 70–79, 80–89 and 90+ years, prevalence among males was 11.81%, 12.03% and 7.56% respectively, compared with 11.76%, 10.58% and 6.38% among females. Prevalence of COPD in SIMD 1 (most deprived) was almost 3.5 times of that in SIMD 5 (least deprived). Adjusting for age and sex, SES inequalities in COPD increased with SIMD1 prevalence 4.8 times that of SIMD5. After adjustment for age sex and ever smoked, SIMD1 prevalence was 3.1 times that of SIMD5. After adjustment for age, sex and current smoking, SIMD1 prevalence was 2.45 times that of SIMD5. Conclusion: Prevalence of COPD in GGC is higher than previously estimated. It is also higher among females than males at ages 50–70 years. Inequalities in COPD are evident and become greater on adjustment for age and sex. Smoking accounts for around half of the gap in prevalence of COPD between most and least deprived, however inequalities in COPD persist after adjustment for smoking status.